Targeted α-therapy of metastatic castration-resistant prostate cancer with 225Ac-PSMA-617: dosimetry estimate and empiric dose finding - Kratochwil, Clemens; Rathke, Hendrik; Haberkorn, Uwe; Giesel, Frederik L. (Journal of nuclear medicine, 2017)
The aim of this study was to develop a treatment protocol for 225Ac-PSMA-617 α-radiation therapy in advanced-stage, metastatic castration-resistant prostate cancer patients with prostate-specific membrane antigen (PSMA)-positive tumor phenotype. Methods: A dosimetry estimate was calculated on the basis of time-activity curves derived from serially obtained 177Lu-PSMA-617 scans extrapolated to the physical half-life of 225Ac, assuming instant decay of unstable daughter nuclides. Salvage therapies empirically conducted with 50 (n = 4), 100 (n = 4), 150 (n = 2), and 200 kBq/kg (n = 4) of 225Ac-PSMA-617 were evaluated retrospectively regarding toxicity and treatment response. Eight of 14 patients received further cycles in either 2- or 4-mo intervals with identical or deescalated activities. Results: Dosimetry estimates for 1 MBq of 225Ac-PSMA-617 assuming a relative biologic effectiveness of 5 revealed mean doses of 2.3 Sv for salivary glands, 0.7 Sv for kidneys, and 0.05 Sv for red marrow that are composed of 99.4% α, 0.5% β, and 0.1% photon radiation, respectively. In clinical application, severe xerostomia became the dose-limiting toxicity if treatment activity exceeded 100 kBq/kg per cycle. At 100 kBq/kg, the duration of prostate-specific antigen decline was less than 4 mo, but if therapy was repeated every 2 mo patients experienced additive antitumor effects. Treatment activities of 50 kBq/kg were without toxicity but induced insufficient antitumor response in these high-tumor-burden patients. Remarkable antitumor activity by means of objective radiologic response or tumor marker decline was observed in 9 of 11 evaluable patients. Conclusion: For advanced-stage patients, a treatment activity of 100 kBq/kg of 225Ac-PSMA-617 per cycle repeated every 8 wk presents a reasonable trade-off between toxicity and biochemical response.